From antimicrobial to anticancer: unraveling the potential of pleurocidin and pleurocidin-derived peptides in the treatment of cancers - Piktel, Ewelina; Wnorowska, Urszula; Gorbacz-Konończuk, Joanna; Sienkiewicz, Jakub; Głuszek, Katarzyna; Okła, Sławomir; Bucki, Robert (Frontiers in Pharmacology, 2024)
Antimicrobial peptides (AMPs), commonly referred to as host defense peptides, are found in a wide range of organisms, including bacteria, plants, and both vertebrate and invertebrate animals. They function as an initial defense mechanism against pathogenic microorganisms, modulate immune responses, and in specific instances, confer protection against the onset of cancer. Pleurocidin (Ple) is a linear antimicrobial peptide with amphipathic α-helical conformation, isolated originally from the winter flounder (Pleuronectes americanus), notable for its wide-ranging effectiveness against both bacteria and fungi. While the majority of research on pleurocidin's biological characteristics has primarily focused on deciphering its mechanisms of interaction with the biological membranes of pathogenic bacteria and host cells, as well as investigating its modes of killing activities, there is a growing body of evidence suggesting that pleurocidin and pleurocidin-derived analogs might be effectively employed as anti-cancer agents against breast carcinoma and leukemia due to their potent cytotoxic properties and selectivity towards cancer cells. Notably, some characteristics of pleurocidin observed in microbiological investigations of this compound could be effectively applied in examining the anti-cancer capabilities of Ple-like derivatives. This review provides a comprehensive overview of the literature on the biological activities of pleurocidin, pleurocidin-derived peptides, pleurocidincontaining hybrid peptides, and nanosystems. The primary emphasis is placed on elucidating the range of activities exhibited by these compounds, evaluating their potential therapeutic applications, assessing their safety profile, and identifying any limits observed thus far. This paper will also discuss potential areas for further investigation into the anti-cancer effects of Ple and its derivatives, drawing insights from microbiological research.